2008
DOI: 10.1186/cc7088
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Bim and Bid gene expression during accelerated apoptosis in severe sepsis

Abstract: Introduction In transgenic animal models of sepsis, members of the Bcl-2 family of proteins regulate lymphocyte apoptosis and survival of sepsis. This study investigates the gene regulation of pro-apoptotic and anti-apoptotic members of the Bcl-2 family of proteins in patients with early stage severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 50 publications
4
51
0
1
Order By: Relevance
“…Our current study strongly suggests that lymphocytes (and not monocytes) drive this pro-apoptotic gene expression profile in unseparated circulating mononuclear cells. In accordance, BCL2 protein expression was reported to be downregulated in CD4+ T cells of patients with sepsis [22] .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our current study strongly suggests that lymphocytes (and not monocytes) drive this pro-apoptotic gene expression profile in unseparated circulating mononuclear cells. In accordance, BCL2 protein expression was reported to be downregulated in CD4+ T cells of patients with sepsis [22] .…”
Section: Discussionsupporting
confidence: 52%
“…A very recent study, using microarrays with 1 50,000 transcripts, showed enhanced activation of genes involved in apoptosis in peripheral blood mononuclear cells of sepsis patients [21] . Moreover, in a separate study, sepsis patients displayed gene expression profiles in whole-blood leukocytes compatible with increased apoptosis [22] . These investigations did not provide insight regarding the contribution of apoptotic mediators in purified leukocyte subsets.…”
mentioning
confidence: 91%
“…Interestingly, Weber and colleagues have recently described a massive upregulation of proapoptotic factors in circulating blood cells from patients suffering from severe sepsis (40). They further concluded that the proapoptotic pattern of gene expression must be generated by lymphocytes, displaying increased apoptosis in sepsis, rather than neutrophils with prolonged life span (40). However, this work demonstrates that the gene expression of most pro apoptotic genes such as Bax, Bad, and Bid is also upregulated in neutrophils after major trauma showing prolonged life span.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, if the comparisons were restricted to a particular cell class, such as circulating lymphocytes or monocytes, a much better correlation of the genomic response between mice and humans might have existed. In this regard, the dramatic upregulation in mouse lymphocytes of the genes encoding pro-apoptotic B cell lymphoma 2 (BCL-2) family members and downregulation of genes encoding anti-apoptotic BCL-2 family members has also been documented in lymphocytes from patients with sepsis 170,171 . The significance of this correlation for a particular class of genes in mice and humans is highlighted by the fact that apoptosis is a key pathogenic mechanism in sepsis.…”
Section: Figurementioning
confidence: 99%